EFFECT OF CELLULASE ENZYMES AND SWELLING AGENTS ON COLOUR STRENGTH (K/S) AND COLOURFASTNESS PROPERTY OF HANDLOOM COTTON FABRIC DYED WITH BUTEA FRONDOSA DYE - Dixit, Sunita (International Journal of Research -GRANTHAALAYAH, 2015)
Cellulase and swelling agents are known to be effective in improving the colour strength of cotton. Nowadays, the handloom fabrics are much preferred due to development of innovative designs and their comfort in wearing Due to increased environmental awareness the use of natural dyes are much preferred in dyeing of handloom fabrics. But, khadi cotton has some major shortcomings like less dyeability. Keeping in view that the pretreatment of khadi cotton with cellulases, swelling agents and combination of cellulases and swelling agents before dyeing improves the colour strength properties, the present study was planned. The khadi cotton samples were treated with optimized conditions of enzymes and swelling agents. The optimum pH, concentration, treatment time and temperature selected for the acid cellulase enzyme treatment were 5.5, 1.5% (owf), 45 minutes and 50°C, respectively whereas in case of neutral cellulase enzyme, it was 7.5, 2.0% (owf), 70 minutes and 70°C respectively. The optimum concentration, treatment time and temperature selected for sodium hydroxide treatment were 20% w/v, 60 minutes and 60°C, respectively. In case of ethylenediamine, 80% w/v, 60 minutes and 70°C were selected as optimum concentration, treatment time and temperature, respectively. In case of zinc chloride treatment, the optimum concentration, treatment time and temperature were selected as 80% w/v, 60 minutes and 70°C. 5 g Butea frondosa dye extracted for 75 minutes gave best results on khadi cotton when dyeing was carried out for 90 minutes It was observed that out of various concentrations of mordants used with Butea frondosa dye, best shades of colour were obtained by using 0.04 g of Alum, 0.01 g of Copper sulphate, 5 g each of Baboolbark.On optimizing the method of mordanting, best results were obtained with Butea frondosa dye when samples were simultaneous mordanted and dyed with Alum, Babool bark and Alum. Pre-mordanting was selected for Copper sulphate. . It was found that for all the enzyme treated (acid and neutral cellulase) as well as swelling agents treated (Sodium hydroxide, Ethylenediamine and Zinc chloride) samples, the colour strength and colourfastness was increased in comparison to the untreated samples.